IN VITRO ANTAGONISM OF INDIGENOUS TRICHODERMA ISOLATES AGAINST PHYTOPATHOGEN CAUSING WILT OF LENTIL: Life Science-Microbiology - SHARFUDDIN, CHOUDHARY; MOHANKA, REENA (International Journal of Life Science and Pharma Research, 2012)
The basic aim of the work was to assess the indigenous potential of bio-agents and their antagonistic potential against phytopathogen viz: Fusarium oxysporum f.sp. lentis; causing wilt of lentil, a disease prevalent in Bihar. In this research work nineteen isolates of Trichoderma were isolated and these were ascribed to three species namely: Trichoderma harzianum (Th), Trichoderma viride (Tv) and Trichoderma koningii (Tk). Efficacy of these bio-antagonists were investigated in in vitro conditions by employing dual culture technique and liquid culture filtrate assay. The outcome of in vitro dual culture testing revealed that among the different isolates of Trichoderma isolate-5 and 7 of Th, 2 and 18 of Tv and isolate 9 of Tk were found to be more efficient amongst all, as they showed better antagonism against the tested phytopathogen.. The isolate Th-5 caused maximum inhibition (82.8%) followed by Th-7 (82.3% ), Tv-2(79.2%) Tv-18 (74.4%) and Tk-9 (71.0%). Rest isolates were moderate in activity. Metabolites extracted from liquid culture filtrates also depicted almost the same trend of superiority as mentioned in dual culture i.e. the same isolates further proved its better potentiality when compared with rest, Th-5 with superior bio-antagonistic potential.